2001
DOI: 10.1089/104303401750195935
|View full text |Cite
|
Sign up to set email alerts
|

A New-Generation Stable Inducible Packaging Cell Line for Lentiviral Vectors

Abstract: We have successfully generated and characterized a stable packaging cell line for HIV-1-based vectors. To allow safe production of vector, a minimal packaging construct carrying only the coding sequences of the HIV-1 gag-pol, tat, and rev genes was stably introduced into 293G cells under the control of a Tet(o) minimal promoter. 293G cells express the chimeric Tet(R)/VP16 trans-activator and contain a tetracycline-regulated vesicular stomatitis virus protein G (VSV-G) envelope gene. When the cells were grown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 45 publications
0
91
0
Order By: Relevance
“…3 However, the high fusogenicity of VSV-G causes rapid syncytia formation and cell death, making it difficult to generate stable cell lines expressing the protein. 4 A number of groups have generated stable packaging and producer cell lines using VSV-G, but in all cases a repressible or inducible promoter regulates the expression of VSV-G. [4][5][6] While regulated expression avoids the problem of VSV-G cytotoxicity, it makes stable production of viral vectors more complicated and cell line generation more timeconsuming.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, the high fusogenicity of VSV-G causes rapid syncytia formation and cell death, making it difficult to generate stable cell lines expressing the protein. 4 A number of groups have generated stable packaging and producer cell lines using VSV-G, but in all cases a repressible or inducible promoter regulates the expression of VSV-G. [4][5][6] While regulated expression avoids the problem of VSV-G cytotoxicity, it makes stable production of viral vectors more complicated and cell line generation more timeconsuming.…”
Section: Introductionmentioning
confidence: 99%
“…The level of regulation provided by coTetR, and the rate that vector is produced post-induction seems to be superior to other inducible systems, particularly the Tet-Off system, in which leaky expression was seen in the off-state. 16,21 Furthermore, the Tet-Off system relies on withdrawal of dox/tetracycline to relieve repression which takes a minimum of 4 days to induce vector production, 16,[18][19][20]25 and up to 13 days to reach maximal levels. 20 In this study, vector production is observed within 24 h of induction.…”
Section: Inducible Eiav-vector Producer Cell Lines Hj Stewart Et Almentioning
confidence: 99%
“…Stable packaging and producer cell lines have been developed for the production of human immunodeficiency virus 1-based LVs [14][15][16][17][18][19][20][21][22][23][24][25] but, to date, none have been described for EIAV-based LVs. The glycoprotein of the vesicular stomatitis virus (VSV-G) is often used for pseudotyping LVs because of its high stability, broad tropism and generation of high-titre viral stocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…117 A similar method, but with all the viral genes expressed from regulated promoters was also recently described. 118 Lentiviral vectors based on viruses other than HIV-1 have been made including HIV-2, 119 bovine, 120 feline, 121 and simian 122,123 lentiviruses. Simian lentivirus system was successfully used for human DC transduction.…”
Section: Lentiviral Vectorsmentioning
confidence: 99%